Some recently found Greek poems : text and commentary - Bremer, Jan Maarten. (Mnemosyne, Supplements, 1987)
This book deals with some (fragmentary) poems of Alcaeus, Archilochus, Hipponax and Stesichorus. The choice of the poems was determined by external factors: all of them are written on papyrus and were first published during the last few decades. After the first edition the fragments were discussed by many scholars, mainly in periodicals. The authors of this volume have assembled the results of this scholarly work and used it as a foundation for a carefully contituted text and an extensive overall commentary. In this way the poems will be more easily accessible than they were hitherto.